Схема образования пакетов стружки при глубоком безвыводном сверлении литейных алюминиев - Маршуба, Вячеслав Павлович (Харьковский государственный политехнический университет, 1999)
Scheme forming and growth of tightly packed packets of chip in chip flutters of twist drills at deer one passed drilling of holes in base members made of cast aluminum alloys on the transfer machines and automatic lines.
Keywords: станок агрегатный; линии автоматические; обработка механическая; инструмент режущий